2020
DOI: 10.1111/ggi.13961
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its associated factors among older persons in Malaysia

Abstract: Aim Quality of life (QoL) among the older persons provides valuable insights into the potential modifiable risk factors that affect well‐being in later life. This study aimed to describe the QoL and psychosocial factors of QoL of older persons in Malaysia. Methods We used the 19‐item Control, Autonomy, Self‐realization and Pleasure scale, a validated instrument that measures psychological well‐being related to QoL in older persons. Scores range from 0 to 57, and higher scores indicate better QoL. We included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…In addition, the following variables are predominantly perceived as risk factors concerning both disability and QOL: being single/unmarried and living without a partner [71,[76][77][78], facing constraints regarding socioeconomical status [27,[79][80][81], as well as social participation and support [20,[82][83][84], malnutrition and under-or overweight [70,85,86], limited physical activity [68,87,88], comorbidities [68,87,89,90] and a low self-rated health status [49,91,92]. Moreover, disability serves as a risk factor for QOL, while a reduced QOL also poses a threat to independent functioning [31,45,68,93].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the following variables are predominantly perceived as risk factors concerning both disability and QOL: being single/unmarried and living without a partner [71,[76][77][78], facing constraints regarding socioeconomical status [27,[79][80][81], as well as social participation and support [20,[82][83][84], malnutrition and under-or overweight [70,85,86], limited physical activity [68,87,88], comorbidities [68,87,89,90] and a low self-rated health status [49,91,92]. Moreover, disability serves as a risk factor for QOL, while a reduced QOL also poses a threat to independent functioning [31,45,68,93].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their functionality is burdened, thus having direct serious effects on their psychological, social, and financial situation. The consequence of all these is a decrease in their self-esteem and self-confidence, feeling as though they are not meeting their social role and social obligations, and ultimately not feeling that they are a “useful” member of society [ 5 ]. Organic changes, physical changes, loneliness, and reduced sexual function may be the reasons for their emotional disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Data from these surveys yielded a sizable literature on CASP (Bowling & Stenner, 2011; Chen & Chen, 2017; Grant & Bowling, 2011; Higgs et al, 2003; Khan & Tahir, 2014; Sexton et al, 2013; Sim et al, 2011; Wiggins et al, 2008; Wu et al, 2013). While most CASP studies were conducted in Europe, such studies have also been done in several Asian countries (Abdul Mutalip et al, 2020; Amit & Litwin, 2010; Damri & Litwin, 2016; Ganapathy et al, 2020; Heravi-Karimooi et al, 2018; Y.-J. Kim & Kang, 2020; Lane et al, 2020; Levin, 2013; Litwin et al, 2017; Nalathamby et al, 2017; Ramli et al, 2020; Wu et al, 2013, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a study conducted in neighboring Singapore found no significant ethnic differentials in QoL (Lane et al, 2020). Apart from socioeconomic variables and perceived health status, Abdul Mutalip et al (2020) found that activities of daily living (ADL) and instrumental activities of daily living (IADL) are also significant predictors of the QoL of older adults in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%